Maoïsme et éducation partisane. L’utopie éducative et la Révolution Culturelle - Roland Depierre (Éducation et Socialisation)
In 2013, a journal published an article entitled Earnest Apologies, in which a former Red Guard offered apologies to the teachers he had disgraced and tortured and to the classmates whose houses he had wrecked during The Great Proletarian Cultural Revolution (1966-1976. ‘I was 14 years old and I was spellbound’ did he admit, while accepting his own responsability. However, no previous time in history had allocated such a preval,ent role to education. It meant to Change Man and to re-educate men, to abolish the Three Great differences separating workers from peasants, cities from rural areas, and intellectuals from manual workers; it also aimed at reducing the Three separations isolating the intelligentsia from proletarian politics, and from peasant and working class life. Finally, it intended to radically transform the intellectuals’ ideology through the assimilation of dialectical materalism. Such goals demanded that any form of neutrality, be it political, axiological, epistemological or pedagogical, be condemned and vilipended. With no regard for the long Chinese cultural tradition of self-discipline, of appropriate distance, of impartiality and of a no-interference (Wuwei) stance, Maoist totalitarianism destroyed the State’s sovereign functions and the principles of equality in education. The revolutionary logic of Education, Re-education, Thought Reform and Overthrowing class domination was a near-impossible task.